The Role of Secretaries in the Adaptation to New Habits - Asa Dian Novianti; Caecilia Tri Wahyanti (Universitas Pendidikan Ganesha, 2021)
During the adaptation period to new habits, he faced two new work systems that caused the company secretary to experience difficulties due to changes in the company. These changes lead to further tasks and new technologies that secretaries must reach in helping managers to facilitate lessons. This study aims to identify the difficulties encountered in adapting to new habits, how to use them during the application, the applications used to complete assignments, and the skills needed by secretaries in the adaptation era. This research was conducted using qualitative research methods. Data were collected from interviews with three secretaries from three different companies. The findings show several obstacles, including delays experienced due to the rules of working from home, the obligation to carry out by following health protocols, and being responsible for health protocols in the workplace. In the running, these secretaries use various applications, such as Microsoft Office, Zoom or WebEx, and E-Archive tools. Therefore, they are expected to be able to utilize technology, be detail-oriented, have administrative skills, operate computers, and communicate in English. This research is expected to be helpful by increasing the knowledge of future secretaries who plan to work during new habits and office management studies.